IMPLEMENTASI LAYANAN VIRTUAL AKIBAT COVID-19 TERHADAP PUSTAKAWAN DAN PEMUSTAKA DI PERPUSTAKAAN POLITEKNIK NEGERI PADANG - Ratnawati Ratnawati (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2023)
This study aims to see the effect of virtual service implementation on librarians and users at the Padang State Polytechnic Library. This study used a descriptive method with a qualitative approach through three paths: reduction, presentation of data and then drawing conclusions. The data were obtained from 5 informants from librarians and 5 informants from users. The parameters observed were the positive impact of virtual services on librarians and library users, the negative impact of virtual services on librarians and users, the obstacles encountered while running virtual services, and the productivity of librarians during the COVID-19 pandemic. Based on the research results, it can be seen that the positive impact of virtual services for librarians is that they can provide a sense of security while working, because they do not interact directly with users so that it is possible to prevent transmission and increase in cases of COVID-19. Meanwhile, the positive impact for users is that virtual account services create comfortable conditions from the risk of contracting Covid-19 and are more free to enjoy library digitization implemented at the Padang State Polytechnic Library. The negative impact of virtual services felt by librarians is the difficulty in carrying out work due to limited mastery of technology, especially for librarians who are elderly. while the negative impact felt by users is that there are economic limitations to buying internet quota and internet access which is hard to come by. The obstacle faced by librarians is the lack of knowledge about using applications and technology that makes them work long hours, bored and lazy as a result they cannot finish work easily, while the obstacle faced by users is limited internet access at their place of residence. The productivity of librarian performance during the COVID-19 pandemic was that 4 of the informants stated that it had decreased because they could not do the job thoroughly, while 1 of the informants stated that it had increased.